Conflicts and peace initiatives between minority Muslims and Thai Buddhists in the Southern Thailand - Abdullah @ Chuah Hock Leng, Osman (Plowshares, 2010)
Until the eighteenth century, the territory that is now Thailand was ruled in waves by Malays, Khmer, Mon, Burmese, Ayutthaya, and Thais. The history of contemporary Thailand begins in 1782 when the capital was established at Bangkok by Thais under King Rama 1. Over the next century, borders were in flux and territory was lost and gained in conflicts and treaties with neighbors, though Thailand boasts being the only nation in Southeast Asia to resist colonization by the French or the British. In 1909, the southern states of Songkla, Patani, Narathiwat, Yala, and parts of Kelantan, Perlis and Kedah were under the Sultan of Patani in Malaya but subject to the influence of the Thai. The Patani Sultanate was strong for a short time but at a later stage it become weak and was forced to pay homage to the Thai king in the form of bunga emas, a plant made of real gold. By the time of the Angelo-Thai agreement in 1909, Songkla, Patani, Narathiwat and Yala were given to Thailand by British colonizers who ceded the land without consultation with the people. Perhaps, the British believed they could obtain enough raw material, such as tin and rubber, from the remaining Malaysian states, which produced sufficient amounts for export of raw materials to Great Britain. Moreover, the Malay states of Kelantan, Kedah, and Perlis provinces on the Malay Peninsula accepted the British, but the people of Yala, Narathiwat and Patani held to their ethnic identity and customs as Malays and Muslims.[1]